2014
DOI: 10.1371/journal.pone.0084239
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Trend of Influenza-Associated Morbidity and the Impact of Early Appearance of Antigenic Drifted Strains in a Southeast Asian Country

Abstract: Globally, influenza infection is a major cause of morbidity and mortality in the elderly, who are suggested to be the major target group for trivalent influenza vaccine (TIV) vaccination by World Health Organization. In spite of an increasing trend in vaccine coverage rates in many countries, the effect of vaccination among the elderly in reducing hospitalization and mortality remains controversial. In this study, we conducted a historical cohort study to evaluate the temporal pattern of influenza-associated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Our previous study suggested that the TIV-receiving group had a higher propensity score of being vaccinated than the non-receiving group. 11 To assess the true effect of revaccination on the influenza-associated hospitalization with minimum interference from unmeasured confounding factors, we then performed propensity score matching on both vaccination and non-vaccination groups. A total of 38,815 and 40,934 subjects were selected in the propensity score-matched non-vaccination groups in the 2007 and 2008 influenza seasons, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study suggested that the TIV-receiving group had a higher propensity score of being vaccinated than the non-receiving group. 11 To assess the true effect of revaccination on the influenza-associated hospitalization with minimum interference from unmeasured confounding factors, we then performed propensity score matching on both vaccination and non-vaccination groups. A total of 38,815 and 40,934 subjects were selected in the propensity score-matched non-vaccination groups in the 2007 and 2008 influenza seasons, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To cope with a large number of potential confounders, we performed matching to create comparable cohorts with or without trivalent influenza vaccine (TIV) vaccination in the current influenza season based on individual propensity score obtained from the propensity score logistic regression model, as described previously. 11 In brief, potential confounding variables incorporated in the model included both demographic and clinical confounders. The demographicconfounders included age, gender, geographic region of residence, urbanization level of residenceand individual socioeconomic status.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations